A new species of large Cyrtodactylus (Squamata: Gekkonidae) from Melanesia - Oliver, Paul; Tjaturadi, Burhan; _, Mumpuni; Krey, Keliopas; Richards, Stephen (Zootaxa, 2008)
A new species of large Cyrtodactylus is described from lowland rainforest on Batanta Island in the Raja Ampat Archipelago, Papua Barat Province, Indonesian New Guinea. The new species can be distinguished from all other Melanesian Cyrtodactylus by the combination of large size (over 110mm SVL), very robust build, presence of enlarged ventral tubercles below the lateral fold and around the angle of the lower jaw only, and dorsal colouration consisting of three to four irregular dark greyish-brown blotches. It is the second species of Cyrtodactylus known with certainty only from the Raja Ampat Islands. The morphology of the new species places it within the C. loriae group and suggests that it is closely related to Cyrtodactylus irianjayaensis.